Establishing and Financing of a Joint Venture: A commentary on the UN/ECE Guide on legal aspects of international (east-west) joint venture contracts - Scott, Norman (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1988)
This article deals with a Guide prepared by the United Nations Economic Commission for Europe concerning east-west joint ventures. The publication focusses on the issues arising in the establishment and operation of east-west joint ventures in those European members countries of the Council for Mutual Economic Assistance (CMEA) which now allow this form of industrial co-operation in their respective territories — namely, Bulgaria, Czechoslovakia, Hungary, Poland, Romania and the Soviet Union. In parallel with that Guide, the author exposes the importance and the contents of the contract itself with its main provisions.